Notes on Sociology of Globalization - Yanitsky, Oleg N. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The notes contain some comments related to the ongoing debates on sociology of globalization concentrated on U. Becks idea of cosmopolitisation and the shaping of cosmopolitan communities. A forthcoming paradigm shift in social sciences;the definition of cosmopolitanism and the establishment of cosmopolitan communities; what is the first phase of cosmopolitisation showed; an idea and possible scenarios of it realization; critics of cosmopolitisation theory concept; cosmopolitanism vs. corporate (or cluster) nationalism; and what is going now and what should be done are main issues in question.Author concluded that: the evolutionary potential of existing sociology is not exhausted; an anthropological shock should be avoided; much more attention should be given to the study of economic and political sources of current disasters; and that local and global sociologists should be much more active in public arena and environmental politics.